An Exploration of Queer Diasporic Subjectivities in Shani Mootoo’s 'Out on Main Street' - Salcedo González, Cristina (Complutense Journal of English Studies, 2020)
In view of the acute lack of analyses of Indian-Trinidadian queer diasporic subjectivities, this article will focus on Shani Mootoo’s “Out on Main Street” by using a queer diasporic theoretical framework, one which hinges on unveiling the violent practices to which sexually and racially marginalized communities are exposed and on exploring the ways by which queer diasporic subjects subvert dominant assumptions. In order to carry out the analysis, I will, first, offer an overview of the uses and implications for invoking the concept of a queer diaspora to study Mootoo’s story; second, I will scrutinize the manner in which the queer diasporic narrator is affected by exclusivist definitions of gender and national identities, and, third, I will examine the specific tactics through which she unsettles the normative logic. Ultimately, the study of Mootoo’s story under a queer diasporic approach will offer a further insight into the diaspora experience, one which considers both sexuality and translocation as crucial factors shaping the way the narrator inhabits the city.